Characteristics of nursing homes and early preventive measures associated with risk of infection from COVID-19 in Lazio region, Italy: a retrospective case–control study - Leonardo Palombi; Alessio Abbondanzieri; Stefano Orlando; Tuba Mazhari; Gennaro Cerone; Fausto Ciccacci; Giuseppe Liotta; Sandro Mancinelli; Maria Cristina Marazzi (BMJ Open)
Objectives To understand which organisational–structural characteristics of nursing homes—also referred to as long-term care facilities (LTCFs)—and the preventative measures adopted in response to the pandemic are associated with the risk of a COVID-19 outbreak.Setting LTCFs in Lazio region in Italy.Design The study adopts a case–control design.Participants We included 141 facilities and 100 provided information for the study. Cases were defined as facilities reporting a COVID-19 outbreak (two or more cases) in March–December 2020; controls were defined as LTCFs reporting one case or zero. The exposures include the structural–organisational characteristics of the LTCFs as reported by the facilities, preventative measures employed and relevant external factors.Results Twenty facilities reported an outbreak of COVID-19. In binary logistic regression models, facilities with more than 15 beds were five times more likely to experience an outbreak than facilities with less than 15 beds OR=5.60 (CI 1.61 to 25.12; p value 0.002); admitting new residents to facilities was associated with a substantially higher risk of an outbreak: 6.46 (CI 1.58 to 27.58, p value 0.004). In a multivariable analysis, facility size was the only variable that was significantly associated with a COVID-19 outbreak OR= 5.37 (CI 1.58 to 22.8; p value 0.012) for larger facilities (>15 beds) versus smaller (<15 beds). Other characteristics and measures were not associated with an outbreak.Conclusion There was evidence of a higher risk of COVID-19 in larger facilities and when new patients were admitted during the pandemic. All other structural–organisational characteristics and preventative measures were not associated with an outbreak. This finding calls into question existing policies, especially where there is a risk of harm to residents. One such example is the restriction of visitor access to facilities, resulting in the social isolation of residents.